Structural Evaluation for Distribution Networks with Distributed Generation Based on Complex Network - Fei Xue; Yingyu Xu; Huaiying Zhu; Shaofeng Lu; Tao Huang; Jinling Zhang (Complexity)
Structural analysis based on complex network theory has been considered promising for security issues of power grids. At the same time, modern power distribution networks with more Distributed Generations (DGs) and Energy Storage Systems (ESS) have taken on more challenges in operation and security issues. This paper proposed a dedicated metric named as Power-Supply-Ability for power distribution networks based on net-ability. Special features of DGs, such as relations of capacities, identification of effective supply area, and limitation in continuous power supply, have been considered in definition. Furthermore, a novel opinion is proposed that the extent of improvement for operation and security by adding DGs also depends on the original structure of the distribution networks. This is an inherent ability of the original networks and could be quantitatively analyzed. Through case studies, this method has been proved to be effective in identifying potential structural vulnerabilities of distribution networks; particularly the impact of DGs on security has been studied. Furthermore, it can help in site selection for DGs by providing different priorities of locations compared with results of other works. This can help to complement other methods to construct a more comprehensive methodology by considering aspects of security, economy, and quality.